Citation and referencing in research writing publication: A guide for selecting the reference management software - Malla, Ashesh; N Shah, Jay; Giri, Bibek; Khadka, Kamal; Gurung, Sanyukta (Journal of Chitwan Medical College, 2025)
Students and individual researchers in medical school and academia face the challenge of managing vast literature, citations and referencing in research writing a publication. Efficient, accurate citation and reference management are crucial. Among many ‘reference management software (RMS)’ available, Zotero, Mendeley, and EndNote are some of the popular choices. This review evaluates these three RMS across nine criteria. Zotero’s accessibility, EndNote’s collaborative teamwork, and Mendeley’s PDF-centricity fulfil the needs of different audiences. A practical recommendation will benefit from choosing RMS tools for scholarly research writing and publication, especially in low- and middle-income countries where availability, cost, ethical values and institutional support vary widely.